Picture dictionary Mandarin Chinese the everyday world at your fingertips - Tracanelli, Carine; Marchwica, Barbara (Berlitz Publishing, 2019)
"With over 2000 essential words and phrases, this stylish, pocket-sized Chinese picture dictionary from Berlitz's trusted language experts makes communicating quick and easy. Developed by a team of Berlitz language experts, each book in this stylish series of picture dictionaries is a goldmine of over 2000 illustrated words and phrases. Packed with essential words you'll need to communicate in everyday situations."--Amazon.com